2006
DOI: 10.2193/0091-7648(2006)34[1184:ubtdpt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Using Baits to Deliver Pharmaceuticals to Feral Swine in Southern Texas

Abstract: Few studies have evaluated oral delivery systems of pharmaceuticals (e.g., vaccines, fertility control agents, and toxicants) to feral swine (Sus scrofa) in the United States. Our objective was to assess, through a field trial, the percentage of feral swine and nontarget animals that remove and consume baits intended to transport pharmaceuticals to feral swine in southern Texas, USA. We hand‐placed 1,178 iophenoxic acid (IA)—marked baits distributed over 1,721 ha (68 baits/km2) in April 2005 and monitored spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 36 publications
(46 reference statements)
1
58
1
Order By: Relevance
“…Bait delivery studies have used concentrations of IPA between 20 and 40 mg/bait (Fletcher et al 1990;Mitchell 1998;Fleming et al 2000;Campbell et al 2006). Twenty milligrams of IPA per bait may be insufficient to detect bait consumption in adult animals or when they consume one bait only (Cowled et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bait delivery studies have used concentrations of IPA between 20 and 40 mg/bait (Fletcher et al 1990;Mitchell 1998;Fleming et al 2000;Campbell et al 2006). Twenty milligrams of IPA per bait may be insufficient to detect bait consumption in adult animals or when they consume one bait only (Cowled et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Percentages of wild boar and feral pigs sampled in the sites where Et-IPA-marked baits have been distributed vary from 31% (in one of the three study sites of Fleming et al (2000)) to 95% (Fletcher et al 1990). Mitchell (1998) found 63% of adult feral pigs eating marked baits whereas Campbell et al (2006) and Cowled et al (2006) reached 74% and 73% of the feral pigs sampled, respectively.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, coyotes removed more fishflavored baits without raccoon repellent than expected, and white-tailed deer removed more vegetable-flavored baits without raccoon repellent than expected. In the United States, raccoons are the primary nontarget animal that remove baits intended to deliver pharmaceuticals to feral swine (Fletcher et al, 1990;Campbell et al, 2006). In the current study, we found the addition of allyl isothiocyanate-and capsaicinoid-based raccoon repellent to baits did not reduce bait removal rates by raccoons, further illustrating the attractiveness of PIGOUT baits and demonstrating the complexity of designing a feral swine-specific oral delivery system in United States with its diverse assemblage of omnivores.…”
Section: Discussionmentioning
confidence: 99%
“…When applied at a density of 35 baits/ha, 85% of recaptured possums had indications of bait uptake; this figure was increased to 100% uptake by doubling the baiting density. Both of these baiting densities are markedly higher than those used in wildlife vaccine delivery programs for either mesocarnivores or porcines (Rosatte and Lawson, 2001;Blackwell et al, 2004;Campbell et al, 2006); however, it must be appreciated that possums reach much higher population densities in New Zealand bush because of their utilization of a tree canopy habitat and their monopolization of the browsing niche, thus requiring a higher baiting density. There are estimated to be over 70 million possums in New Zealand, with population densities over 2,000 animals per km 2 reported in favorable broadleaf forest habitats (Efford, 2000).…”
Section: Discussionmentioning
confidence: 99%